Peranan Hukum dalam Mencegah Praktik Politik Uang (Money Politics) dalam Pemilu di Indonesia: Upaya Mewujudkan Pemilu yang Berintegritas - M Jeffri Arlinandes Chandra; Jamaludin Ghafur (Wajah Hukum, 2020)
The presence of a political party in the modern constitutional system is one of the necessity as one of the institutions authorized to fill the political position/power. The filling of the department/Power referred to one must be done through the mechanism of direct selection by the people is to fill the legislative office (DPR, DPD and DPRD) and executives (Presidents and regional heads). Thus, the political parties and the elections are two things that must be mandatory in a democratic state. A problem that always arise in the election is money politic. The majority of the advanced candidates run for the head of the political parties – allegedly strong – always involve material/money to win it. The practice of money politic in the Indonesian system of participation and election is believed to be one of the reasons for the quality and performance of democratic institutions in Indonesia, especially the political parties and parliaments. This kind of thing needs to be identified on what is the factor that causes the political money (money politics) and the necessity of the role of the ideal law (legislation) in providing solutions in reducing or even (when possible) preventing the occurrence of political money (money politics). The type of research used is juridical normative legal research, which is legal research conducted by examining the library material. There are 3 (three) reasons for the emergence of political practice money (money politics) in the elections, namely: (i) Patron-client, poverty factor, low Party-ID. The role that can be taken by the law in preventing the political practice of money is (i) required the policy to impose criminal sanctions only for money politic. (ii) Change the legislative election system from a proportional system to the district system.